The Rationalism and Empiricism in the Islamic Perspective and Their Relevance to Islamic Education - Sya’ban, Bildan Muhammad; Sheleisya, Adinda Hasna; Parhan, Muhamad (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
Islamic education faces the challenge of balancing various sources of knowledge, including rationalism, empiricism and revelation. Rationalism emphasizes reason as the primary means of acquiring knowledge, while empiricism relies on sensory experience. Islam recognizes both approaches, but places revelation as the highest foundation. The lack of balance in the application of these three elements can have an impact on the quality of Islamic education. This research uses a qualitative approach with a literature study method to examine the thoughts of Muslim figures such as Al-Farabi, Ibn Sina, and Al-Ghazali. They offer a synthesis between rationalism, empiricism and revelation in building a holistic education system. The results show that the balance between reason, experience and revelation is an important foundation for the development of Islamic education. With proper integration, Islamic education can accommodate the development of science and technology without neglecting spiritual values. The findings confirm that the harmonization of these three elements is the main key in improving the quality of Islamic education in the modern era.